Copy number variation of ubiquitin- specific proteases genes in blood leukocytes and colorectal cancer. Issue 7 (2nd July 2020) - Tian, Tian; Bi, Haoran; Liu, Yupeng; Li, Guangxiao; Zhang, Yiwei; Cao, Liming; Hu, Fulan; Zhao, Yashuang; Yuan, Huiping
ABSTRACT: Ubiquitin-specific proteases (USPs) play important roles in the regulation of many cancer-related biological processes. USPs copy number variation (CNVs) may affect the risk and prognosis of colorectal cancer (CRC). We detected CNVs of USPs genes in 468 matched CRC patients and controls, estimated the associations between the USPs genes CNVs and CRC risk and prognosis and their interactions with environmental factors on CRC risk. Finally, we generated five CRC risk predictive models with different CNVs patterns combining with environmental factors (EF). We identified significant association between CYLD deletion and CRC risk (ORadj  = 4.18, 95% CI: 2.03–8.62), significant association between USP9X amplification and CRC risk (ORadj  = 2.30, 95% CI: 1.48–3.57), and significant association between USP11 deletion and CRC risk (ORadj  = 3.49, 95% CI: 1.49–8.64). There were significant gene-environment and gene–gene interactions on CRC risk. The area under the receiver operating characteristic curve (AUC) of EF + SIG (deletion of CYLD and USP11, amplification of USP9X) model was significantly larger than any other models (AUC = 0.75, 95% CI: 0.74–0.77). We did not identify significant associations between CNVs of the three genes and CRC prognosis. CNVs of CYLD, USP9X, and USP11 are significantly associated with the risk of CRC. Gene-gene and gene–environment interactions might also play an important role in the development of CRC.